Review of the Gargara genistae (Fabricius, 1775) species group (Hemiptera: Membracidae) from Russia and adjacent territories - Tishechkin, Dmitri Yu. (Zootaxa, 2022)
In Russia, Kazakhstan, and Central Asia the Gargara genistae species group includes three species differing from each other in the male calling signal patterns, but almost indistinguishable in external appearance and the male genitalia shape. Illustrated descriptions of morphology and the male calling signals, and data on host plants and distribution for all species are given. Considerations concerning possible modes of species divergence in this group are provided.